100 Jahre Musikvideo: Eine Genregeschichte vom frühen Kino bis YouTube - Lilkendey, Martin (transcript, 2017)
From the Paris World Fair of 1900 to Elvis Presley to MTV and the current 'Generation YouTube' – for the first time, Martin Lilkendey traces in detail the complete history of the music video in the western world. Starting with a precise definition of the popular short music film and based on a wealth of examples, this introduction film-historically brackets early cinema with YouTube, spelling out in what sense the history of the music video is also a history of the media. The precise categorisation of the music video as an independent genre of its own outside of the music film, as well as the empirical-descriptive approach allow the book to take a much broader historic scope than all other previous academic treatments of the subject.